Effect of tensile stress on metal magnetic memory signals during on-line measurement in ferromagnetic steel. (January 2021) - Wang, Huipeng; Dong, Lihong; Wang, Haidou; Ma, Guozheng; Xu, Binshi; Zhao, Yuncai
Abstract: Metal magnetic memory testing (MMMT) is a promising nondestructive technique for early damage evaluation of ferromagnetic materials due to its high sensitivity to the stress state. An experimental investigation of the effect of axial applied stress on MMMT signals, both the normal component B z and the tangential component B x, under on-line loaded and unloaded measurement condition has been carried out during the whole tensile test in 0.45%C steel. In the elastic deformation stage, B z signal kept rotating counterclockwise while B x signal kept moving upward under on-line measurement both when loaded and unloaded, but the MMMT signals measured unloaded tended to resume the initial state compared those measured loaded. In the plastic deformation stage, B z signal rotated clockwise while B x signal moved downward under on-line loaded measurement with the increase of tensile stress, while the MMMT signals measured unloaded reversed compared those measured loaded. The results of the present work indicate that MMMT is a feasible solution for stress state on-line monitoring of ferromagnetic components.